2021
DOI: 10.1016/j.intimp.2021.108242
|View full text |Cite
|
Sign up to set email alerts
|

Does prior exposure to immune checkpoint inhibitors treatment affect incidence and mortality of COVID-19 among the cancer patients: The systematic review and meta-analysis

Abstract: Background Immune checkpoint inhibitors (ICIs) treatment among cancer patients has been shown to have antiviral effects by reactivating exhausted T cells. However, they could also trigger inflammatory storm. Therefore, prior exposure to ICIs may influence the risk of SARS-CoV2 infection and subsequent mortality. Recent results from studies of ICIs treatment on incidence and mortality of COVID-19 are controversial. Materials and methods We searched databases PubMed, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
3
8
0
1
Order By: Relevance
“…In this study, compared with other cancer treatments, ICI treatment neither increased the incidence of COVID-19 (OR 0.84; 95% CI 0.60-1.18) nor the mortality (OR 1.22; 95% CI 0.91-1.62). 37 Other previous systematic reviews showed similar results. [38][39][40] Lazarus et al [38] searched through February 2021 and evaluated other clinical outcomes besides mortality; however, they included 11 studies for analysis, compared with 21 included in our review.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study, compared with other cancer treatments, ICI treatment neither increased the incidence of COVID-19 (OR 0.84; 95% CI 0.60-1.18) nor the mortality (OR 1.22; 95% CI 0.91-1.62). 37 Other previous systematic reviews showed similar results. [38][39][40] Lazarus et al [38] searched through February 2021 and evaluated other clinical outcomes besides mortality; however, they included 11 studies for analysis, compared with 21 included in our review.…”
Section: Discussionsupporting
confidence: 67%
“…Our results are consistent with other studies. The most recent systematic review was that published by Liu et al,[ 37 ] with a search performed through May 2021 reporting incidence and mortality. In this study, compared with other cancer treatments, ICI treatment neither increased the incidence of COVID-19 (OR 0.84; 95% CI 0.60-1.18) nor the mortality (OR 1.22; 95% CI 0.91-1.62).…”
Section: Discussionmentioning
confidence: 99%
“…These findings received further support in a prospective study of 292 melanoma patients on ICIs, where treatment was not found to increase the risk of severe infection [ 62 ], as was the case in a large real world study of 228 patients receiving ICIs vs. 456 non-ICI treated patients, where no significant difference in COVID-19 mortality or disease severity was found [ 63 ]. These results were further corroborated by several meta-analyses investigating the incidence and mortality of COVID-19 in patients with prior exposure to an ICI [ 64 , 65 ].…”
Section: Covid-19supporting
confidence: 54%
“…[24][25][26][27] Last, a number of meta-analyses have pooled studies to assess whether exposure to ICIs affects severe outcomes or mortality in patients with COVID-19 and cancer. [28][29][30][31] For instance, Liu et al 28 pooled data from 19 studies that had an ICI-treated group and a comparator group and showed no association of ICI treatment on mortality (odds ratio, 1.22; 95% CI, 0.91-1.62; p ¼ .18;…”
Section: Covid-19 Outcomes In Patients With Cancermentioning
confidence: 99%